UNDERSTANDING DYSPEPSIA IN PATIENTS WITH PARKINSON’S DISEASE - Doina, Georgescu; Mihaela, Simu; Daniel, Lighezan (European Scientific Journal, ESJ, 2013)
﻿Objectives: Better understanding dyspepsia in Parkinson’s disease (PD) in order to improve patients quality of life. Methods: 27 patients (17 men,10 women, mean age=68,11± 12,62 years) diagnosed with PD (Hoehn-Yars scale), treated with levodopa or dopamine agonists, with gastrointestinal autonomic disorders and disturbances of gastric motility assessed by ultrasound approach undertook a trial consisting of a treatment with Trimebutine 300 mg/day for 3 months. We have assessed digestive severity symptoms scores before and after therapy: no symptoms=0, mild=1, medium=2, severe=3, comparing also to gastric motility curves. Results: Before therapy 15 patients showed delayed of the gastric emptying (55,56%), 7 normal motility (25,92%) and 5 patients rapid emptying (18,51%).Symptoms severity scores before therapy were: 8 patients (29,52%) mild ,14 patients (51,85%) medium and 5 patients (18,51%).severe. Mean dyspepsia severity index in patients with gastric motility disorders before therapy was 2,20±0,52.After therapy the same index decreased to 1,50±0,69(p=0,0009).Gastric motility curves showed an improving after therapy more important in those with delaying emptying varying with 23,45%±14,03 versus 15%±5,87% in patients with rapid emptying (either p<0,001). Conclusions An important range of patients with PD, with nausea and vomiting presented gastric motility disorders (74,07%), most of them having delay of the emptying and a satisfactory response to the treatment with Trimebutine with improving of symptom severity index and also gastric motility.